Depression and Anxiety among Acne and Melasma Patients - Ajay Kumar, Asia Hafeez, Anoop Kumar Juseja, Abdul Ghani Rahimo, Sayed Muhammad Shahkar Ali, Ghulam Shabir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of depression and anxiety in acne and melasma patients presented at dermatology OPD of a tertiary care Hospital. Material and methods: This cross-sectional study was conducted at the dermatology OPD of Sir Syed Hospital Qayoomabad. Patients with acne or melasma, aged 18 years or above, both gender, patients who have not received treatment for depression or anxiety in the last 3 months and Patients who are willing to complete the study questionnaire honestly and to the best of their ability were included. Hospital Anxiety and Depression scale (HADS) was used to assess the anxiety and depression in study subjects All the data was recorded in self-made proforma and analysis was done by using SPSS version 26. Results: A total of 93 individuals were studied, regarding anxiety and depression due to acne and melasma. Mean age of the participants was 31.32+10.45 years. Females were 64.5% and males were 35.5%. 32.3% of the cases had Melasma and remaining 67.7% had acne. 32.3% cases had mild anxiety, 32.3% had moderate anxiety and 6.5% had severe anxiety. According to the depression, 32.3% cases had mild depression, 19.4% had moderate depression and 19.4% cases had severe depression, while 29.0% cases had no depression. Severity of depression and anxiety were statistically insignificant according to gender, marital status, duration of disease and types of skin disorder (p->0.05). Conclusion: It has been observed that individuals with acne and melasma have a higher likelihood of experiencing symptoms of anxiety and depression. The negative impact of these dermatological conditions on an individual’s self-esteem and overall well-being can be significant, leading to emotional distress and psychological difficulties. Keywords: Anxiety, Depression, Melasma, Acne